Zmiany na europejskim rynku kapitałowym - Wojtasiak-Terech, Agnieszka (Changes on the European Capital Market, 2008)
The goal of the paper is presentation of main changes taking place on the European capital market during last decades. Following reasons of changes are presented: globalization, deregulations, increasing importance of institutional investors and innovations. Te main attention is paid to importance of institutional investors. The research concentrates on the UCITS market in 2002-2006. The author as well paid attention on selected changes on the capital market like stock exchanges consolidations and demutualization. The paper concentrates mainly on the EU financial market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 96-106